KEKUASAAN DAN KORUPSI DI TINGKAT LOKAL - Haboddin, Muchtar (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2011)
This writing sets forth from the comprehension that power is tightly correlated with corruption practice in local level. This understanding is proved herein the parties who are involved in the practice in regional level are the governors and the regional representatives (DPRD). Both of this institutions celebrate massive corruption practice among the implementation of desentralization project. When the transfer of fund is in a quite high amount from central government to the region, the elites are most likely corrupt the fund. This is the irony happens in the reality due to the implementation of desentralization project. Â Keywords: Power, Corruption, Government, and Regional Representative (DPRD).